Tempering high-temperature transparent glass glaze as well as preparation method and application thereof
By optimizing the component materials and preparation process of glass powder, a kind of steel -torbon -to -high -temperature transparent glass glaze is prepared, which solves the problem of insufficient performance of existing high temperature transparent glaze in anti -PID attenuation, acid resistance and tempered tolerance, and realized it. The efficient performance and long -term stable operation of photovoltaic components.
Patent Information
- Application Number
- CN202411375056.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing high-temperature transparent glaze has insufficient performance in terms of PID attenuation, acid resistance and tempering tolerance, and cannot meet the long-term and stable operation of photovoltaic modules.
By optimizing the component material and preparation process of glass powder, a kind of mixed, melting, water quenching, ball milling, ball milling, ball milling, ball milling, ball milling, ball mill grinding To form a glass glaze with excellent physical and chemical properties.
It significantly improves the anti -PID attenuation performance of photovoltaic components, enhances corrosion resistance in an acidic environment, improves tempered tolerance, and extends the service life of photovoltaic components.
Smart Images

Figure CN119371104A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic components, and in particular to a tempered high-temperature transparent glass glaze and a preparation method and application thereof. Background Art
[0002] At present, in the field of BIPV (building integrated photovoltaic), high-temperature transparent glazes are widely used for the surface treatment of photovoltaic glass. This glaze can be sintered at high temperature to form a transparent protective film, which improves the weather resistance and corrosion resistance of photovoltaic modules. However, the high-temperature transparent glazes currently used have the following problems: (1) High sodium oxide content: The sodium oxide content of the existing high-temperature transparent glaze is about 8%. Although it can ensure a certain light transmittance, the excessive sodium oxide content will cause the performance of photovoltaic modules to decay under certain conditions. (2) Insufficient anti-PID decay performance: During operation, photovoltaic modules are easily affected by potential induced decay (PID). When the current high-temperature transparent glaze is tested for anti-PID decay (85°C, 85% RH, -1500V, 192h), the decay rate is about 4.5%. In addition, some modules were damaged during the test, indicating that the PID decay rate of the existing high-temperature transparent glaze is high and cannot meet the needs of long-term stable operation of photovoltaic modules. (3) Insufficient acid resistance: The current high-temperature transparent glaze is easily corroded in an acidic environment and does not have good acid resistance, which limits its application in certain special environments, such as the seaside, chemical plants and other highly corrosive areas. (4) Poor tempering tolerance of acid-resistant glaze: In order to improve the acid resistance of high-temperature transparent glaze, researchers have developed an acid-resistant glaze. However, this acid-resistant glaze has poor tolerance during the tempering process, that is, in the temperature range of 680-720℃, different color hues will appear when tempered at different temperatures, affecting the appearance and performance of photovoltaic modules.
[0003] Therefore, the existing high temperature transparent glaze has deficiencies in anti-PID attenuation, acid resistance and tempering tolerance, and needs to be improved. In view of this, it is necessary to provide an improved temperable high temperature transparent glass glaze and its preparation method and application to solve the above problems. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides a temperable high-temperature transparent glass glaze and its preparation method and application, aiming to solve the technical problems of insufficient performance of high-temperature transparent glaze in terms of anti-PID attenuation, acid resistance and tempering tolerance.
[0005] In a first aspect, the present application provides a method for preparing a tempered high-temperature transparent glass glaze, comprising the following steps:
[0006] S1. Add the component materials of the glass powder into a mixer and mix them evenly to obtain a mixture; the component materials of the glass powder include, by mass percentage: 30-40% silicon dioxide, 1-5% aluminum oxide, 8-10% boron oxide, 35-45% bismuth oxide, 1-5% sodium oxide, 1-5% lithium oxide, 2-6% titanium dioxide, 0.5-2% calcium oxide and 1-3% zinc oxide, and the sum of the components is 100%;
[0007] S2. adding the mixture obtained in step S1 into a furnace, first preheating it, and then melting it to obtain molten glass;
[0008] S3. The glass liquid obtained in step S2 is water quenched to obtain a granular glass frit;
[0009] S4. The granular glass frit obtained in step S3 is dried and ball-milled to obtain glass powder;
[0010] S5. The glass powder obtained in step S4 is sieved, powder larger than 10 μm is collected and step S4 is repeated to obtain a glass powder;
[0011] S6. The component materials of the varnish are mixed evenly, and the vitreous powder obtained in step S5 is added and mixed evenly to obtain a slurry;
[0012] S7. The slurry obtained in step S6 is mixed and ground to obtain a tempered high-temperature transparent glass glaze.
[0013] In the technical solution of the embodiment of the present application, by optimizing the component materials of the glass powder, the anti-attenuation performance of the final glaze can be significantly improved. This means that the prepared photovoltaic module has a lower PID attenuation rate under high temperature, high humidity and electric field, thereby extending the service life of the photovoltaic module. Through the synergistic effect between the components, the final glaze has better corrosion resistance in an acidic environment, which broadens the application range of photovoltaic modules, especially in highly corrosive environments. By accurately controlling the temperature of the furnace and the melting process, as well as subsequent ball milling and screening treatment, a glass glaze with better tempering tolerance can be obtained.
[0014] In some embodiments, the preheating temperature is 550-650° C., and the preheating time is 15-25 min; the melting temperature is 1100-1300° C., and the melting time is 50-70 min.
[0015] In this embodiment, the preheating treatment helps to reduce the temperature gradient inside the material and make the temperature distribution of the entire material more uniform, which is beneficial to the effect of the subsequent melting treatment. The high-temperature melting treatment can ensure that the component materials of the glass powder are fully melted to form a uniform glass liquid, which is beneficial to improving the performance of the final product. By accurately controlling the preheating and melting treatment, a glass glaze with excellent physical and chemical properties can be obtained, such as better heat resistance, transparency and acid and alkali resistance, which are crucial for photovoltaic modules.
[0016] In some embodiments, the material of the ball mill is zirconia, and the ball milling time is 1 to 2 hours.
[0017] In this embodiment, the zirconium oxide ball milling medium has high hardness and wear resistance, and can achieve uniform refinement and dispersion of glass powder in a short time. Fine powder helps to reduce light scattering and improve the transparency of the final product.
[0018] In some embodiments, the mesh number of the sieving process is 1700-1800 mesh. The particle size of the obtained glass powder is less than 10 μm.
[0019] In this embodiment, the screen has very fine meshes, which can effectively separate glass powder with a particle size of less than 10 μm, ensuring that the particle size distribution of the powder is within a very narrow range. By screening with a high-mesh screen, larger particles and impurities can be removed, thereby improving the purity of the powder. Accurately controlled particle size distribution helps optimize the performance of the final product, such as transparency, strength, thermal stability, etc.
[0020] In some embodiments, the component materials of the varnish include, by mass percentage: 60-80% terpineol, 15-25% butyl carbitol, and 5-15% acrylic resin, and the sum of each component is 100%; the mass ratio of the glass powder to the varnish is (70-75):(25-30).
[0021] In this embodiment, these components of varnish can provide good printing performance, ensure that the printing process is carried out smoothly, and reduce printing defects. The mixing of pine alcohol and butyl carbitol can provide appropriate viscosity, so that the varnish can fully wet the glass powder and maintain good fluidity. Acrylic resin, as a binder, helps to improve the dispersibility of glass powder in varnish and prevents powder from agglomerating. Acrylic resin can also enhance the adhesion of varnish to the glass surface, which is conducive to subsequent printing or coating processes. At the same time, acrylic resin can form a protective film on the glass surface, improve the durability and weather resistance of the coating. Selecting an appropriate amount of acrylic resin can ensure that the coating maintains a higher transparency after drying, without affecting the photoelectric conversion efficiency of the photovoltaic module.
[0022] In a second aspect, an embodiment of the present application provides a tempered high-temperature transparent glass glaze, which is prepared by the preparation method of the first aspect.
[0023] In a third aspect, the embodiment of the present application provides a double-glass photovoltaic module, which is composed of a front glass, an adhesive film, a battery cell and a back glass. The surface of the front glass is printed with a film including the temperable high-temperature transparent glass glaze described in the second aspect, and the mass fraction of the temperable high-temperature transparent glass glaze in the film is 75-98wt%. By controlling the proportion of the temperable high-temperature transparent glass glaze, a double-glass photovoltaic module with excellent performance can be obtained.
[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 This is a physical picture of the double-glass photovoltaic module prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0027] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0029] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0030] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0031] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0032] The sodium oxide content of the high-temperature transparent glaze in the prior art is about 8%. The test component is PID-resistant (85°C, 85% RH, -1500V, 192h), and the attenuation rate is about 4.5%. In addition, some components were damaged during the test, and the PID attenuation rate was high. The transparent glaze is not acid-resistant and cannot meet the needs of long-term stable operation of photovoltaic components. The tempering tolerance of the acid-resistant glaze is poor, and different color hues will appear when tempered at different temperatures, affecting the appearance and performance of the photovoltaic components.
[0033] In order to solve the technical problems that high-temperature transparent glazes have insufficient performance in terms of anti-PID attenuation, acid resistance and tempering tolerance, the present application provides a temperable high-temperature transparent glass glaze and a preparation method and application thereof, wherein, by optimizing the component materials of the glass powder, the prepared double-glass photovoltaic module has high transparency, good acid resistance, high tempering tolerance, and strong anti-PID attenuation ability.
[0034] In a first aspect, the present application provides a method for preparing a tempered high-temperature transparent glass glaze, comprising the following steps:
[0035] S1. Add the component materials of the glass powder into a mixer and mix them evenly to obtain a mixture; the component materials of the glass powder include, by mass percentage: 30-40% silicon dioxide, 1-5% aluminum oxide, 8-10% boron oxide, 35-45% bismuth oxide, 1-5% sodium oxide, 1-5% lithium oxide, 2-6% titanium dioxide, 0.5-2% calcium oxide and 1-3% zinc oxide, and the sum of the components is 100%;
[0036] S2. adding the mixture obtained in step S1 into a furnace, first preheating it, and then melting it to obtain molten glass;
[0037] S3. The glass liquid obtained in step S2 is water quenched to obtain a granular glass frit;
[0038] S4. The granular glass frit obtained in step S3 is dried and ball-milled to obtain glass powder;
[0039] S5. The glass powder obtained in step S4 is sieved, powder larger than 10 μm is collected and step S4 is repeated to obtain a glass powder;
[0040] S6. The component materials of the varnish are mixed evenly, the vitreous powder obtained in step S5 is added, and the mixture is mixed evenly at a speed of 500 to 550 r / min to obtain a slurry;
[0041] S7. The slurry obtained in step S6 is mixed and ground by a two-roll grinder at a rotation speed of 1800 to 2100 r / min to obtain a tempered high-temperature transparent glass glaze.
[0042] By precisely mixing the different chemical components, a glass glaze is prepared that remains transparent at high temperatures and has good performance during the tempering process. The components interact during the melting, quenching, drying, ball milling and screening processes to form a glass glaze with excellent physical and chemical properties.
[0043] Furthermore, in some embodiments, the temperature of the preheating treatment is 550-650° C., and the preheating time is 15-25 min. The temperature of the melting treatment is 1100-1300° C., and the melting time is 50-70 min.
[0044] In the technical solution of the embodiment of the present application, the purpose of the preheating treatment is to slowly heat the material to a certain temperature to reduce the stress inside the material and prevent the generation of cracks. The melting treatment temperature range and time period ensure that the material can be fully melted and help to improve the uniformity and purity of the material.
[0045] Furthermore, in some embodiments, the ball mill material is zirconia, the ball milling time is 1 to 2 hours, the mesh number of the sieving treatment is 1700 to 1800 mesh, and the particle size of the obtained glass powder is less than 10 μm.
[0046] Glass powder with a particle size of less than 10 μm can ensure high transparency and uniform component distribution in the final product.
[0047] Furthermore, in some embodiments, the component materials of the varnish include, by mass percentage, 60-80% terpineol, 15-25% butyl carbitol, and 5-15% acrylic resin, and the sum of the components is 100%. The mass ratio of the vitreous powder to the varnish is (70-75): (25-30), preferably 72:28.
[0048] In the technical scheme of the embodiment of the present application, pine alcohol helps to dissolve and stabilize other ingredients, butyl carbitol is used to improve the fluidity and stability of the mixture, and also helps to improve the surface finish of the final product, and acrylic resin can improve the viscosity and adhesion of the mixture, which helps the uniform dispersion of glass powder in the glaze. The ratio of vitreous powder and varnish ensures that the glass powder can be well dispersed and stable in the varnish, thereby preparing a uniform, high-quality glaze. A higher ratio of glass powder helps to improve the thermal stability and mechanical properties of the glaze, and the varnish ensures the processability and applicability of the glaze. By accurately controlling these components and ratios, a glass glaze with ideal performance can be prepared, which can provide good transparency, heat resistance and tempering performance when applied to ceramics, glass or other substrate materials.
[0049] In a second aspect, an embodiment of the present application provides a tempered high-temperature transparent glass glaze, which is prepared by the preparation method of the first aspect.
[0050] In a third aspect, the embodiment of the present application provides a double-glass photovoltaic module, which is composed of a front glass, an adhesive film, a battery cell and a back glass. The surface of the front glass is printed with a film including the temperable high-temperature transparent glass glaze described in the second aspect, and the mass fraction of the temperable high-temperature transparent glass glaze in the film is 75-98wt%. By controlling the proportion of the temperable high-temperature transparent glass glaze, a double-glass photovoltaic module with excellent performance can be obtained.
[0051] The preparation method of the double-glass photovoltaic module comprises the following steps:
[0052] The tempered high-temperature transparent glass glaze is evenly mixed with pearlescent powder, structural color powder and color ink, and coated on the glass surface by screen printing. The wet film thickness is 15-25μm. After baking, curing and high-temperature tempering, a colored BIPV front glass is obtained. The mass ratio of the tempered high-temperature transparent glass glaze, pearlescent powder, structural color powder and color ink is (60-90): (1-20): (1-20): (0-10); the curing temperature is 170-200℃, and the curing time is 3-8min; the tempering temperature is 680-720℃, and the tempering time is 120-150s; the front glass is made into a double-glass component through a stacking and laminating process, and the stacking is front glass-film-cell-film-back glass.
[0053] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0054] 1. Preparation method
[0055] Example 1
[0056] This embodiment provides a method for preparing a tempered high-temperature transparent glass glaze, comprising the following steps:
[0057] S1. Add the component materials of the glass powder to the mixer and mix them evenly to obtain a mixture; the component materials of the glass powder include, by mass percentage: 35% silicon dioxide, 3% aluminum oxide, 9% boron oxide, 40% bismuth oxide, 3% sodium oxide, 3% lithium oxide, 4% titanium dioxide, 1% calcium oxide and 2% zinc oxide;
[0058] S2. Add the mixture obtained in step S1 into a furnace, perform preheating treatment first, the preheating temperature is set to 600°C, the preheating time is set to 20min, and then perform melting treatment, the melting temperature is set to 1200°C, the melting time is set to 60min, and a glass liquid is obtained;
[0059] S3. The glass liquid obtained in step S2 is quickly poured into pure water at room temperature for quenching, thereby obtaining a quenched granular glass frit;
[0060] S4. The granular glass frit obtained in step S3 is placed in an electric blast drying oven for full drying and then placed in a ball mill for ball milling. The ball mill material is zirconium oxide and the ball milling time is 1.5 h, so that the obtained glass powder particle size is about 10 μm;
[0061] S5. The glass powder obtained in step S4 is sieved using a vibrating stainless steel sieve with a mesh size of 1800, and powder larger than 10 μm is collected and step S4 is repeated until all powder particles are less than 10 μm to obtain a glass powder;
[0062] S6. The components of the varnish, 70% terpineol, 20% butyl carbitol, and 10% acrylic resin, are mixed uniformly, and the vitreous powder obtained in step S5 is added, wherein the mass fraction of the vitreous powder is 72%, the mass fraction of the varnish is 28%, and the mixture is mixed uniformly at a speed of 500 r / min to obtain a slurry;
[0063] S7. The slurry obtained in step S6 is mixed and ground again by a two-roll grinder at a rotation speed of 2000 r / min to obtain a tempered high-temperature transparent glass glaze.
[0064] The glass glaze prepared in Example 1 is used to prepare a double-glass photovoltaic module, specifically: the glass glaze is evenly mixed with mica-based pearlescent powder and photonic crystal powder in a mass ratio of 95:3:2, and coated on the glass surface by screen printing, with a wet film thickness of 20 μm, and baked and cured at 180°C for 5 minutes, and tempered at 700°C for 120 seconds to obtain a colored BIPV front plate glass; the front plate glass is made into a double-glass module through a lamination and laminating process, and the lamination is front plate glass-adhesive film-cell-adhesive film-back plate glass. The actual picture of the obtained double-glass photovoltaic module is as shown in FIG. Figure 1 shown.
[0065] Example 2
[0066] The present embodiment provides a method for preparing a tempered high-temperature transparent glass glaze. Compared with Example 1, the only difference is that the component materials of the glass powder include, by mass percentage, 34% silicon dioxide, 2% aluminum oxide, 10% boron oxide, 41% bismuth oxide, 3% sodium oxide, 4% lithium oxide, 3% titanium dioxide, 1% calcium oxide and 2% zinc oxide. The other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.
[0067] Comparative Examples 1-5
[0068] Comparative Examples 1-5 respectively provide a method for preparing a tempered high-temperature transparent glass glaze. Compared with Example 1, the only difference is that the component material ratios of glass powder and varnish are different, as shown in Table 2. Other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.
[0069] Comparative Example 6
[0070] Comparative Example 6 provides a glass glaze, whose components, by mass percentage, include: 38% silicon dioxide, 12% zinc oxide, 15% boron oxide, 3% potassium oxide, 3% titanium dioxide, 8% sodium oxide, 18% ethylene glycol, and 3% acrylic resin. The glass glaze is used to prepare a double-glass photovoltaic module according to the method of Example 1 for testing the PID attenuation rate.
[0071] 2. Test Method
[0072] The test methods for the glass glaze properties prepared in various embodiments and comparative examples are shown in Table 1.
[0073] Table 1 Performance test methods of embodiments and comparative examples
[0074]
[0075]
[0076] III. Analysis of test results of various embodiments and comparative examples The test results of the embodiments and comparative examples are shown in Tables 2 and 3.
[0077] Table 2 Performance test results of embodiments and comparative examples
[0078]
[0079]
[0080] Table 3 Test results of toughening tolerance of glass enamel prepared in Example 1
[0081]
[0082] According to the test, the PID attenuation rate of the double-glass photovoltaic module prepared in Example 1 is 1.98%, and the PID attenuation rate of the double-glass photovoltaic module in Comparative Example 6 using the existing glass glaze is 4.35%.
[0083] It can be seen from the test results that the tempered high-temperature transparent glass glaze obtained according to the method provided in the embodiment of the present application has good acid resistance. After being soaked in 5% hydrochloric acid / 5% sulfuric acid for 24 hours, there is no color difference change and no powdering or falling off; there is no color change, no powdering, and no falling off after boiling or soaking in water; the adhesion, peel strength, PCT accelerated aging test and coating hardness all meet the requirements; the transmittance is increased by 1-2% compared with the same period, up to 85%, and the test spectrum range is: 380-1100nm; the tempering tolerance is high, and the color difference value ΔE is less than 1.5 when tempered in the range of 680-720℃; the anti-PID attenuation ability is strong, and the attenuation rate is less than 4% when tested under the conditions of 85℃, 85%RH, -1500V, and 192h.
[0084] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing a tempered high-temperature transparent glass glaze, characterized in that: The following steps are involved: S1. Add the component materials of the glass powder into a mixer and mix them evenly to obtain a mixture; the component materials of the glass powder include, by mass percentage: 30-40% silicon dioxide, 1-5% aluminum oxide, 8-10% boron oxide, 35-45% bismuth oxide, 1-5% sodium oxide, 1-5% lithium oxide, 2-6% titanium dioxide, 0.5-2% calcium oxide and 1-3% zinc oxide, and the sum of the components is 100%; S2. adding the mixture obtained in step S1 into a furnace, first preheating it, and then melting it to obtain molten glass; S3. The glass liquid obtained in step S2 is water quenched to obtain a granular glass frit; S4. The granular glass frit obtained in step S3 is dried and ball-milled to obtain glass powder; S5. The glass powder obtained in step S4 is sieved, powder larger than 10 μm is collected and step S4 is repeated to obtain a glass powder; S6. The component materials of the varnish are mixed evenly, and the vitreous powder obtained in step S5 is added and mixed evenly to obtain a slurry; S7. The slurry obtained in step S6 is mixed and ground to obtain a tempered high-temperature transparent glass glaze.
2. The method for preparing the tempered high temperature transparent glass enamel according to claim 1, characterized in that: In step S2, the preheating temperature is 550-650°C, and the preheating time is 15-25 minutes.
3. The method for preparing the tempered high temperature transparent glass enamel according to claim 2, characterized in that: The temperature of the melting treatment is 1100-1300° C., and the melting time is 50-70 minutes.
4. The method for preparing the tempered high temperature transparent glass enamel according to claim 1, characterized in that: In step S4, the ball milling time is 1 to 2 hours.
5. The method for preparing the tempered high temperature transparent glass enamel according to claim 1, characterized in that: In step S5, the mesh size of the sieve used in the sieving process is 1700-1800 meshes.
6. The method for preparing the tempered high temperature transparent glass enamel according to claim 5, characterized in that: The particle size of the obtained glass powder is less than 10 μm.
7. The method for preparing the tempered high temperature transparent glass enamel according to claim 1, characterized in that: In step S6, the component materials of the varnish include, by mass percentage, 60-80% of terpineol, 15-25% of butyl carbitol, and 5-15% of acrylic resin, and the sum of the components is 100%.
8. The method for preparing the tempered high temperature transparent glass enamel according to claim 7, characterized in that: The mass ratio of the glass powder to the varnish is (70-75):(25-30).
9. A temperable high temperature transparent glass glaze, characterized in that: The glass glaze is prepared by the method for preparing the tempered high-temperature transparent glass glaze according to any one of claims 1 to 8.
10. A double-glass photovoltaic module, characterized in that: The invention is composed of a front glass plate, an adhesive film, a battery cell and a back glass plate. The surface of the front glass plate is printed with a film comprising the tempered high temperature transparent glass glaze according to claim 9, and the mass fraction of the tempered high temperature transparent glass glaze in the film is 75-98wt%.
Citation Information
Patent Citations
Low-melting-point glass powder as well as preparation method and application thereof
CN110818269A
Acid-resistant high-temperature-resistant ink for glass and preparation method thereof
CN112551910A
Lead-free glass powder, glass black glaze and preparation methods of lead-free glass powder and glass black glaze
CN113754274A
Environment-friendly high-reflection ink coating for photovoltaic glass and preparation method of environment-friendly high-reflection ink coating
CN116239312A
Laminated glaze-plated layer suitable for photovoltaic module, preparation method of laminated glaze-plated layer, photovoltaic backboard semi-tempered glaze-plated glass and photovoltaic module
CN117550808A